Implementasi Pembelajaran Kitab Ta`limul Muta`allim Dalam Membentuk Sikap Takzim Santri Kepada Ustaz di Pondok Pesantren Nurul Iman Cisalak - Ajat Saputra; Septiana Gumelar; OlinRizky Zazuli; Shaleh Afif (Jurnal Pendidikan Educandum, 2025)
This attitude of reverence is motivated because a student is not enough to seek religious knowledge but must obey and respect his ustaz. This study aims to analyze the implementation of learning the Ta`limul Muta`allim book, analyze the form of the attitude of Reverence of students, analyze the Implementation of Learning the Ta`limul Muta`allim Book, analyze the supporting factors and inhibiting factors in forming the attitude of Reverence of students and analyze the success in forming the attitude of Reverence of students to ustaz. This study uses qualitative research methods. The methods used are qualitative and descriptive approaches. Researchers collect data through Observation, Interviews, Documentation, and Questionnaires. Data Analysis Techniques used by Researchers are Data Reduction, Data Presentation and Conclusions. The results of this study indicate that in general, facilitating the process of forming a reverent attitude in the daily lives of students, the environment of the Islamic boarding school is one of the influences on the reverent attitude, as well as the participation of the ustadz in practicing the reverent attitude and the length of the students' habituation in practicing the reverent attitude of students which are supporting and inhibiting factors in the formation of the reverent attitude of students and the success of the reverent attitude of students is influenced by 2 factors, namely external and internal.